2012
DOI: 10.1186/1471-2105-13-s10-s18
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for detecting the orthology signal in a PPI network at a functional complex level

Abstract: BackgroundStable evolutionary signal has been observed in a yeast protein-protein interaction (PPI) network. These finding suggests more connected regions of a PPI network to be potential mediators of evolutionary information. Because more connected regions of PPI networks contain functional complexes, we are motivated to exploit the orthology relation for identifying complexes that can be clearly attributed to such evolutionary signal.ResultsWe proposed a computational methodology for detecting the orthology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…This suggests that presence of evolution in modularity of PPI networks is more versatile and flexible with different degrees of conservation. The findings of Jancura et al (2011) seem to conform with related studies that focused on evolutionary cohesiveness of protein functional modules in order to investigate whether a group of proteins which functionally interact, co-evolve more cohesively than a random group of proteins. Either known protein complexes and pathways were analysed (Fokkens & Snel, 2009;Seidl & Schultz, 2009;Snel & Huynen, 2004) or putative protein modules usually derived from integrated networks of functional link evidences (Campillos et al, 2006;Zhao et al, 2007;Zinman et al, 2011).…”
Section: Evolution and Modularity Of Ppi Networksupporting
confidence: 63%
See 1 more Smart Citation
“…This suggests that presence of evolution in modularity of PPI networks is more versatile and flexible with different degrees of conservation. The findings of Jancura et al (2011) seem to conform with related studies that focused on evolutionary cohesiveness of protein functional modules in order to investigate whether a group of proteins which functionally interact, co-evolve more cohesively than a random group of proteins. Either known protein complexes and pathways were analysed (Fokkens & Snel, 2009;Seidl & Schultz, 2009;Snel & Huynen, 2004) or putative protein modules usually derived from integrated networks of functional link evidences (Campillos et al, 2006;Zhao et al, 2007;Zinman et al, 2011).…”
Section: Evolution and Modularity Of Ppi Networksupporting
confidence: 63%
“…The finding that modularity of PPI networks is constrained by evolution and that conserved interactions are enriched in dense motifs and regions of a PPI network also suggest that protein complexes present in such cohesive areas should be evolutionary driven (Jancura et al, 2011). As putative protein complexes can be extracted from a PPI network by means of clustering techniques, Jancura et al (2011) detected such protein complexes in the PPI network consisting of only yeast proteins having an ortholog in another organism and compared them with those protein complexes derived either by using the global topology of a yeast PPI network or by using a network induced by randomly selected proteins. The in-depth examination of enriched functions in these three types of protein complexes revealed that evolutionary-driven complexes are functionally well differentiated from other two types of protein complexes found in the same interaction data.…”
Section: Evolution and Modularity Of Ppi Networkmentioning
confidence: 99%
“…In the PPI networks, the detection of protein complexes, or functional modules, is an ongoing challenge, but it is crucial for revealing the mechanism of biological functions and providing a valuable guide for comprehending the processes controlling cell life. In addition, detecting protein complexes can be useful for defining the evolutionary orthology signal, such as for the prediction of protein functions based on their biological functions that have not yet been identified, and most crucially, for medical uses [9,10]. It is noteworthy to mention that proteins that interact with one another can be categorized as either "protein complexes" or "functional modules," each of which having a distinct biological significance.…”
Section: Introductionmentioning
confidence: 99%
“…Protein–protein interaction (PPI) networks in multicellular organisms, such as humans, often include a larger number of cellular proteins relative to networks found in monocellular eukaryotic organisms ( Evlampiev and Isambert 2008 ; Jancura et al. 2012 ; Jin et al.…”
Section: Introductionmentioning
confidence: 99%